A novel kind of tumor type-characteristic junction: plakophilin-2 as a major protein of adherens junctions in cardiac myxomata - Rickelt, Steffen; Rizzo, Stefania; Dörflinger, Yvette; Zentgraf, Hanswalter; Basso, Cristina; Gerosa, Gino; Thiene, Gaetano; Moll, Roland; Franke, Werner (Modern pathology, 2010)
Using novel antibodies of high avidity to—and specificity for—the constitutive desmosomal plaque protein, plakophilin-2 (Pkp2), in a systematic study of the molecular composition of junctions connecting the cells of soft tissue tumors, we have discovered with immunocytochemical, biochemical and electron microscopical methods, a novel type of adherens junctions in all 32 cardiac myxomata examined. These junctions contain cadherin-11 as their major transmembrane glycoprotein, which we could repeatedly show in colocalization with N-cadherin, anchored in a cytoplasmic plaque formed by α- and β-catenin, together with the further armadillo-type proteins plakoglobin, p120, p0071 and ARVCF. Surprisingly, all adherens junctions of these tumors contained, in addition, another major armadillo protein Pkp2, hitherto known as an obligatory and characteristic constituent of desmosomes in epithelium-derived tumors. We have not detected Pkp2 in a series of noncardiac myxomata studied in parallel. Therefore, we conclude that this acquisition of Pkp2, which we have recently also observed in some mesenchymally derived cells growing in culture, can also occur in tumorigenic transformations in situ. We propose to examine the marker value of Pkp2 in clinical diagnoses of cardiac myxomata and to develop Pkp2-targeted therapeutic reagents.
Online verfügbar 27. August 2010, Artikelversion 4. Januar 2023
Gesehen am 15.05.2023